Necessary and sufficient conditions for eventually vanishing oscillatory solutions of functional equations with small delays - Bhagat Singh (International Journal of Mathematics and Mathematical Sciences)
Necessary and sufficient conditions are found for all oscillatory solutions of the equation (rn−1(t)(rn−2(t)(−−−(r2(t)(r1(t)y′(t)))−−−)))+a(t)h(y(g(t)))=b(t) to approach zero. Sufficient conditions are also given to ensure that all solutions of this equation are unbounded.